The dependence of cosmic ray driven galactic winds on halo mass - Jacob, Svenja; Pakmor, Rüdiger; Simpson, Christine M.; Springel, Volker; Pfrommer, Christoph (Arxiv, 2017)
Galactic winds regulate star formation in disk galaxies and help to enrich the circum-galactic medium. They are therefore crucial for galaxy formation, but their driving mechanism is still poorly understood. Recent studies have demonstrated that cosmic rays (CRs) can drive outflows if active CR transport is taken into account. Using hydrodynamical simulations of isolated galaxies with virial masses between $10^{10}$ and $10^{13}\mathrm{~M_\odot}$, we study how the properties of CR-driven winds depend on halo mass. CRs are treated in a two-fluid approximation and their transport is modelled through isotropic or anisotropic diffusion. We find that CRs are only able to drive mass-loaded winds beyond the virial radius in haloes with masses below $10^{12}\mathrm{~M_\odot}$. For our lowest examined halo mass, the wind is roughly spherical and has velocities of $\sim20\mathrm{~km\;s^{-1}}$. With increasing halo mass, the wind becomes biconical and can reach ten times higher velocities. The mass loading factor drops rapidly with virial mass, a dependence that approximately follows a power-law with a slope between $-1$ and $-2$. This scaling is slightly steeper than observational inferences, and also steeper than commonly used prescriptions for wind feedback in cosmological simulations. The slope is quite robust to variations of the CR injection efficiency or the CR diffusion coefficient. In contrast to the mass loading, the energy loading shows no significant dependence on halo mass. While these scalings are close to successful heuristic models of wind feedback, the CR-driven winds in our present models are not yet powerful enough to fully account for the required feedback strength.